Inovasi PRO GALO untuk Meningkatkan Kompetensi dan Pembelajaran Pemeliharaan Pakaian Pelindung - Abdullah, Anton; Komalasari, Yeti; Nugraha, Wildan; Hermala, Zusnita; Amalia, Direstu; Firdaus, Muhammad Bayu El; Rahmawaty, Indah Nur; Fadli, M. (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
This research aims to enhance the maintenance practices of Aircraft Rescue and Fire Fighting (ARFF) protective clothing through the implementation of the Proficient Rinse and Optimal Garment Laundering (PRO GALO) system, which integrates advanced washing and rinsing techniques. Utilizing a Research and Development (R&D) approach, this study systematically developed a prototype based on the analysis, design, development, implementation, and evaluation model. The findings reveal that the PRO GALO system significantly improves garment cleanliness, odor removal, and durability compared to traditional laundering methods. Quantitative assessments demonstrated superior performance in preserving fabric integrity, colorfastness, and seam strength. Feedback from ARFF personnel and cadets indicated high satisfaction rates, highlighting the system's user-friendliness and time-saving advantages. Expert validation further emphasized the innovative aspects of the system, enhancing safety and operational readiness in emergency response situations. The implications for ARFF operations and the Aviation Fire and Rescue Study Program stress the importance of integrating advanced cleaning technologies to prepare future professionals better. Ultimately, the PRO GALO system represents a significant advancement in ensuring reliable protective gear for ARFF personnel.